HOSPITAL INFECTIONS IN THE POST-PARTUM PERIOD: A LITERATURE REVIEW OF THE MAIN RISK FACTORS, PREVENTION, AND INTERVENTION (CIPEEX, 2025)
Postpartum infections are quite common and pose a serious risk to maternal life and health, contributing significantly to maternal mortality rates in Brazil and worldwide. The objective of this study is to conduct a literature review to identify the main risk factors associated with postpartum hospital infections, in addition to evaluating evidence-based prevention and intervention strategies to improve maternal health and the quality of hospital care. This is a narrative literature review study. The search will be conducted in the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Evidence in Health in Latin America and the Caribbean (BIREME/PAHO/WHO), and PubMed, as well as academic repositories and manuals from the Ministry of Health, published in full between 2019 and 2024. The results indicate that risk factors such as cesarean sections, prolonged rupture of membranes, and inadequate aseptic practices are determinants of postpartum hospital infections. It is concluded that collaboration among health professionals in the prevention of postpartum infections is of paramount importance for developing and applying effective prevention strategies and implementing these essential measures to reduce the incidence of puerperal infections and improve maternal health in the postpartum period.
Keywords: Risk factors; Hospital infections; Intervention; Postpartum; Prevention